Emotion dysregulation as a mechanism linking child maltreatment exposure and self-harm behaviors in adolescents. (May 2017) - Peh, Chao Xu; Shahwan, Shazana; Fauziana, Restria; Mahesh, Mithila V.; Sambasivam, Rajeswari; Zhang, YunJue; Ong, Say How; Chong, Siow Ann; Subramaniam, Mythily
Abstract: Although child maltreatment exposure is a recognized risk factor for self-harm, mechanisms underlying this relationship remain unclear. Self-harm may function as a compensatory strategy to regulate distressing emotions. This cross-sectional study examines if emotion dysregulation mediates between the severity of maltreatment exposure and self-harm, adjusting for demographic variables and depressive symptoms. Participants were 108 adolescent patients recruited from a psychiatric hospital in Singapore (mean age 17.0 years, SD = 1.65; 59.3% female). Study measures included the Childhood Trauma Questionnaire (CTQ-SF), Functional Assessment of Self-Mutilation (FASM), Difficulties in Emotion Regulation Scale (DERS), and the Patient Health Questionnaire (PHQ-8). Path analysis was conducted to examine the direct and indirect effects of maltreatment exposure on self-harm via emotion dysregulation, controlling for demographic variables and depressive symptoms. Indirect effects were tested using bootstrapped confidence intervals (CI). Results showed that self-harm was highly prevalent in our sample (75.9%). Emotion dysregulation and depressive symptoms were found to be associated with higher self-harm frequency. In addition, results from path analysis showed that the association between the severity of maltreatment exposure and self-harm frequency was significantly mediated by emotion dysregulation B = 0.07, p < 0.05, 95% CI [0.02, 0.16]. Thus, emotion dysregulation may be a proximal mechanism linking maltreatment exposure and adolescent self-harm. Notably, self-harm may represent maladaptive attempts to manage emotion dysregulation that may have resulted from maltreatment. Findings from the study have implications for the prevention and treatment of self-harm in maltreated youth.